55.6k views
1 vote
2a – 3c = –6

a + 2c = 11

1 Answer

3 votes

For the first equation the solution for 'A'

- Move all terms that don't contain a to the right side and solve. a = −3 + 3c/2

And the solution for 'C' (It's still the same equation..)

- Move all terms that don't contain c to the right side and solve. c = 2 + 2a/3

Then as for the second one, the solution for 'A'

- Subtract 2c from both sides of the equation. a = 11 − 2c

As for the 'C' is..

- Move all terms that don't contain c to the right side and solve. c = 11/2 − a/2

____

I hope this helps, as always. I wish you the best of luck and have a nice day, friend..

User Nfadili
by
5.5k points